SOSIALISASI PROSES PRODUKSI POPCORN - Taufik, Moh (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2022)
The socialization of the popcorn production was carried out to 10 participants from Sungai Liku Tangah Village, Nagari Sungai Liku Pelangai, Ranah Pesisir District. Socialization was implemented through social media i.e. YouTube and WhatsApp group. The stages of socialization activities consist of a preparation stage and an implementation stage. In the preparation stage, the speakers prepared several things i.e. popcorn formula, popcorn packaging, video presentation, materials and tools. At the implementation stage, the speakers presented several materials to the participants, namely an overview of corn, the popcorn production, packaging of popcorn, and finally determining the shelf life of popcorn. In general, the socialization can increase the knowledge of participants about the popcorn production process. This can be seen from several questions asked by the participants.